Casein‐specific IL‐4‐ and IL‐13‐secreting T cells: a tool to implement diagnosis of cow's milk allergy. Issue 11 (30th August 2014) - Michaud, B.; Aroulandom, J.; Baiz, N.; Amat, F.; Gouvis‐Echraghi, R.; Candon, S.; Foray, A.‐P.; Couderc, R.; Bach, J.‐F.; Chatenoud, L.; Just, J.
Abstract Background Cow's milk allergy (CMA) is a frequent food allergy in young children. The oral food challenge is the gold standard for diagnosis, and there is currently no reliable biological test. Our aim was to evaluate the diagnostic potential of a functional assay quantifying allergen‐specific Th2 cells in CMA children. Methods A total of 29 children aged 2.8–10.5 years underwent a double‐blind, placebo‐controlled food challenge (DBPCFC) to cow's milk. Blood was collected before performing the DBPCFC, and peripheral mononuclear cells were cultured in an 18‐h ELISpot assay with casein, α‐lactalbumin, or β‐lactoglobulin. Numbers of antigen‐specific IL‐4‐ and IL‐13‐secreting lymphocytes and serum‐specific IgE, IgG4, and total IgE levels were assessed. Receiver operating characteristic (ROC) curves were generated. Results A total of 17 (59%) children reacted to cow's milk and were therefore considered as allergic to cow's milk (CMA). The mean number of casein‐specific IL‐4‐ and IL‐13‐secreting T cells was higher in CMA than in non‐CMA children (P = 0.009, 0.004, respectively). Moreover, it was inversely correlated with the cumulative dose of cow's milk tolerated (P = 0.003, 0.0009, respectively). ROC curve of combined IL‐4 and IL‐13 analysis showed an area under the curve of 0.98 (95% CI 0.90–1.06). For a cutoff of 10 IL‐4‐ and 12 IL‐13‐secreting T cells, sensitivity and negative predictive value were 100%. Conclusions Enumeration of casein‐specific IL‐4‐ and IL‐13‐secreting T cells appears a promising tool to improve diagnosis and, if confirmed in larger studies, could permit less frequent use of the oral food challenge.